Curricular training report: 7 months as a study coordinator at Blueclinical LTD - In-Uba, Mariana José Manuel (2016)
The present report describes in detail the activities undertaken under the coordination of clinical and observational studies during the curricular internship at Blueclinical Ltd., inserted in the Master of Pharmaceutical Biomedicine. Blueclinical Ltd.company operates in three different areas: R&D consultancy, management and coordination of trial centers, and a phase I unit. The curricular internship had the duration of seven months during which I was able to perform different tasks relating to coordination of clinical trials in Centro Hospitalar do Baixo Vouga, E.P.E., (CHBV) in Aveiro, Portugal. This academic internship allowed me to develop theoretical and practical skills in the field of clinical trials and observational studies. I also had the opportunity to further the knowledge I gained throughout my academic journey. During this internship, I had the opportunity to interact with different health professionals and develop my knowledge in the field of several therapeutic indications. I also could interact with distinct monitors and sponsors. This experience allowed me to improve time management, communication and problems resolution skills.